A review of the oriental genus Praepristus (Coleoptera: Carabidae: Platynini). Issue 6 (19th March 2015) - Fedorenko, Dmitry N.
Abstract: The holotype of Praepristus nepalensis Kirschenhofer, 1999 (Coleoptera: Carabidae: Platynini), the type species of the genus, is revised and it actually shows all basic characters of Platynini, not Lebiini: Pericalina as considered before. The genus is redescribed, based on fresh material, and the new transfer to the tribe Platynini is briefly discussed. Ten new species are described: P. caviceps new species, P. depressus new species, P. foveiceps new species, P. grandis new species, P. kabakovi new species, P. similis new species, P. sulcifer new species, P. testaceus new species, and P. tonkinensis new species all from Vietnam, and P. borneensis new species from Sabah, Borneo, Malaysia. Both Colpodes planus Landin, 1955 and Notagonum rugifoveatus Louwerens, 1955 are newly transferred to Praepristus Kirschenhofer, 1999. A key to all 13 currently known species of the genus is given. Résumé: L'holotype de Praepristus nepalensis Kirschenhofer, 1999 (Coleoptera: Carabidae: Platynini), l'espèce type du genre, est révisé et il présente en effet tous les caractères principaux des Platynini, mais pas ceux des Lebiini: Pericalina, comme il était considéré précédemment. Le genre est re-décrit à partir de matériel frais et le transfert dans la tribu de Platynini est brièvement discuté. Dix nouvelles espèces sont décrites: P. caviceps nouvelle espèce, P. depressus nouvelle espèce, P. foveiceps nouvelle espèce, P. grandis nouvelle espèce, P. kabakovi nouvelle espèce, P. similis nouvelle espèce, P. sulcifer nouvelle espèce, P. testaceus nouvelle espèce, et P. tonkinensis nouvelle espèce du Viêt-Nam, et P. borneensis nouvelle espèce, du Sabah (Borneo, Malaisie). Les espèces Colpodes planus Landin, 1955 et Notagonum rugifoveatus Louwerens, 1955 sont transférées pour la première fois au genre Praepristus Kirschenhofer, 1999 . Une clé pour l'identification des 13 espèces actuellement connues du genre est proposée.